Test anxiety and its determinants among health sciences students at Mattu University: a cross-sectional study - Jarso, Mohammedamin Hajure; Tariku, Mandaras; Mamo, Aman; Tsegaye, Tesfaye; Gezimu, Wubishet (Frontiers in Psychiatry, 2024)
Background: Test anxiety is a particular type of anxiety that is marked by physical, cognitive, and behavioural symptoms when taking and performing tests. It is defined as "severe stress" before, during, and after exams and other assessments. Test anxiety could cause poor academic performance and increase dropout rates. This study aimed to determine the levels of test anxiety and its determinants among health sciences students at Mattu University.Methods: An institution-based cross-sectional study was conducted among 421 selected students from June 1 to June 30, 2021. The study utilized the Westside Test Anxiety, the Oslo Social Support Scale, the Rosenberg Self-esteem Scale, and the Kessler Scale to assess test anxiety, social support, self-esteem, and psychological distress, respectively. The collected data were entered into EpiData version 3.1 and then exported to STATA version 14.0 for analysis. A linear regression model was used to determine the correlation between psychological factors and test anxiety. The multiple regression assumptions were checked for each variable. Statistically significant effects were assumed for a p-value of less than 0.05 at a 95% confidence interval in the multiple linear regression analysis. Formatted: Line spacing: single Results: A total of 416 (99%) participants were completed out of the 420 questionnaires administered. The mean score of test anxiety among participants was 25.3 (SD: ±5.51). Tobacco use (β: 1.028; 95% CI: 0.709-1.347), khat chewing (β: 0.115; 95% CI: 0.038-0.192), self-esteem